Analysis of Strouhal number based equivalence of pitching and plunging airfoils and wake deflection. (June 2015) - Khalid, Muhammad Saif Ullah; Akhtar, Imran; Durrani, Naveed Iqbal
Numerical simulations have been used to analyze the equivalence of pitching and plunging motions found in a flapping NACA0012 airfoil. Two-dimensional incompressible Navier–Stokes equations are solved at Reynolds number of 10 3 over a range of Strouhal numbers. A novel criterion based on the Strouhal number is proposed which provides equivalence of pitching and plunging motions using the length scale traversed by the trailing edge in each case. Aerodynamic coefficients are found to match well for both the kinematics in temporal as well as spectral domains. Detailed analysis provides contribution of different mechanisms, such as vortex shedding, added mass, interaction of leading and trailing edge vortices, in the overall aerodynamic forces produced by a pitching or plunging airfoil. Wake deflection is observed for a plunging airfoil at high Strouhal numbers resulting in a bias in the lift coefficient. Further investigation reveals the dominance of second harmonic of the fundamental frequency in the lift spectrum emphasizing the role of quadratic nonlinearity in the observed phenomenon.